Hopf Algebras and Integrable Flows Related to the Heisenberg–Weil Coalgebra - Blackmore, D.; Prykarpatsky, A. K.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
On the basis of the structure of Casimir elements associated with general Hopf algebras, we construct Liouville–Arnold integrable flows related to naturally induced Poisson structures on an arbitrary coalgebra and their deformations. Some interesting special cases, including coalgebra structures related to the oscillatory Heisenberg–Weil algebra and integrable Hamiltonian systems adjoint to them, are considered.